Comparison of sparfloxacin, temafloxacin, and ciprofloxacin for prophylaxis and treatment of experimental foreign-body infection by methicillin-resistant Staphylococcus aureus. - Cagni, A (1995)
The prophylactic and therapeutic activities of three broad-spectrum fluoroquinolones were evaluated in two different experimental models of foreign-body infections caused by methicillin-resistant Staphylococcus aureus (MRSA) susceptible to quinolones. In a guinea pig model of prophylaxis, subcutaneously implanted tissue cages were infected at a > 90% rate by 10(2) CFU of MRSA in control animals. A single dose of 50 mg of ciprofloxacin per kg of body weight administered intraperitoneally 3 h before bacterial challenge was less effective than an equivalent regimen of either sparfloxacin or temafloxacin in decreasing the rate of experimental infection in tissue cages challenged with increasing inocula of MRSA. In a rat model evaluating the therapy of chronic tissue cage infection caused by MRSA, the efficacy of a 7-day high-dose (50-mg/kg twice-daily) regimen of sparfloxacin, temafloxacin, or ciprofloxacin was compared to that of vancomycin (50 mg/kg twice daily). Active levels of sparfloxacin, temfloxacin, or ciprofloxacin were continuously present in tissue cage fluid during therapy, exceeding their MBCs for MRSA by 6- to 20-fold. Either temafloxacin, sparfloxacin, or vancomycin was significantly (P < 0.01) more active than ciprofloxacin in decreasing the viable counts of MRSA in tissue cage fluids. The different activities of ciprofloxacin compared with those of the other two quinolones against chronic tissue cage infections caused by MRSA did not involve the selective emergence of quinolone-resistant mutants. Temafloxacin and ciprofloxacin, which showed the most prominent differences in their in vivo activities, however, exhibited similar bactericidal properties and pharmacokinetic parameters in the rat model. In conclusion, both temafloxacin and sparfloxacin were significantly more active than ciprofloxacin for the prophylaxis or treatment of experimental foreign-body infections caused by a quinolone-susceptible strain of MRSA.